Algorithms of the quantitative analysis of images in an information environment of morphological research - K B Gordon (RUDN Journal of Medicine, 2011)
It's necessary to make an effective performance of research work in the conditions of a modern science research automation. This aspect is not realized as full as it need in the Russian medical high schools. Most actual questions of medical education process are introduction and active use of these research automation tools. To solve this problem it is necessary to design some new principles and algorithms of working with them.